Energy system contribution to 1500- and 3000-metre track running - Duffield, R.; Dawson, B.; Goodman, C. (Journal of Sports Sciences, 2005)
The aim of the present study was to quantify the contributions of the aerobic and anaerobic energy systems to 1500- and 3000-m track running events during all-out time-trials performed individually on a synthetic athletic track. Ten 3000-m (8 males, 2 females) and fourteen 1500-m (10 males, 4 females) trained track athletes volunteered to participate in the study. The athletes performed a graded exercise test in the laboratory and two time-trials over 1500 or 3000?m. The contributions of the energy systems were calculated by measures of race oxygen uptake, accumulated oxygen deficit (AOD), race blood lactate concentration, estimated phosphocreatine degradation and some individual muscle metabolite data. The relative aerobic energy system contribution (based on AOD measures) for the 3000 m was 86 % (male) and 94 % (female), while for the 1500 m it was 77 % (male) and 86 % (female). Estimates of anaerobic energy expenditure based on blood lactate concentrations, while not significantly different (P > 0.05), were generally lower compared with the AOD measures. In conclusion, the results of the present study conform with some recent laboratory-based measures of energy system contributions to these events.